Evoked responses to sinusoidally modulated sound in unanaesthetized dogs - Tielen, A.M.; Kamp, A.; Lopes da Silva, F.H.; Reneau, J.P.; Storm van Leeuwen, W. (Elsevier, 1969)
1. 1. Responses evoked by sinusoidally amplitude-modulated sound in unanaesthetized dogs have been recorded from inferior colliculus and from auditory cortex structures by means of chronically indwelling stainless steel wire electrodes. 2. 2. Harmonic analysis of the average responses demonstrated that the energy of most of the responses was concentrated in components at fundamental and second harmonic frequencies. 3. 3. The influence of various stimulus parameters was investigated, in particular the effect of variation of modulation frequency between 10 and 80 c/sec. 4. 4. The amplitude/frequency characteristics of the fundamental components obtained from the inferior colliculus were almost flat, with a slight amplitude decrease at frequencies above 60 c/sec. In some of the cortical areas the characteristics showed a maximum of amplitude at modulation frequencies between 15 and 30 c/sec. 5. 5. The phase/frequency characteristics showed a lag of phase with modulation frequency. From this phase lag delay times were calculated. Those at the inferior colliculus were shorter than those at the auditory cortex. At the latter structure the calculated delay times corresponded closely with latencies of the first positive deflection of responses evoked in these same structures by tone bursts. 6. 6. The amplitude modulation depth characteristics showed that the amplitudes of the responses were influenced by modulation depth. At the inferior colliculus an almost linear relation appeared to exist between modulation depth and response amplitudes.In the auditory cortex more complex relations between modulation depth and amplitude occurred. “Saturation” phenomena were observed in two cortical areas. 7. 7. Restricted investigations into the effects of the composition of the carrier signal revealed that change of carrier signal from sine wave at 4000 c/sec to band-limited noise at 3200–5000 c/sec caused change of the response amplitude distribution over the auditory cortex. Decrease of average intensity to 62 dB produced no change.
Keywords: Geneeskunde